Phantom radio [compact disc] - Lanegan, Mark (Vagrant Records, 2014)
"While this music is, for the most part, noticeably simpler and more pop-oriented than his Soulsavers recordings, songs like 'Waltzing in Blue,' 'The Killing Season,' and 'Floor of the Ocean' manage to sound polished on the surface while Lanegan gives them a rough-hewn gravity, fusing the timeless spirit of classic blues and rural folk songs to music clearly rooted in the 21st century... Phantom Radio shows that a bit more production polish and digital styling hasn't fogged Lanegan's message, and Phantom Radio reveals the singer and his songs are as strong and as eloquent as ever"--Allmusic.com.